Role of consumer referrals in decision making and their role in building online brand communities- Case study 50cycles.com - Khandelwal, Nikita (2011)
Abstract The advent of the World Wide Web has changed completely, the way companies communicate with customers. It is no longer a one way communication, the consumer is heard loud and clear through social media like Facebook, Twitter, review websites, blogs etc. Social media has turned the customer-company relationship on its head. Before doing business with a company, customers research about them using the social media. It is easier to trust one’s peers then to rely on company generated facts especially with multiple companies selling similar products. For high risk products, expert opinion becomes vital. The social media makes all this possible. In this age of consumer empowerment, is it feasible for a company to ignore the social media? Online networking sites provide to members a wide range of opportunity to generate, extend and find peers based on individual interests. As a result, while online members create user-generated content, there is a terrific opportunity for marketers to make use of the ever-increasing social networking population and target their offerings to customised groups. However social media advertising and electronic word of mouth publicity are not without risk since the company has no control over the information presented on such mediums. Also for medium and small businesses, the social media and electronic word of mouth publicity is the most efficient and cost effective tool for reaching out to potential customers. 50cycles.com is one such company and through my dissertation I endeavour to understand how the social media can be leveraged to reach a wider consumer base and build stronger bonds with the existing customers of the company. For this purpose consumers were contacted online to understand how influential are online review websites, blogs and other social media in determining the purchasing behaviour. At the same time the present communication channels of 50cycles.com were studied and accordingly suggestions for improvement were made.